24-h urinary sodium excretion is associated with obesity in a cross-sectional sample of Australian schoolchildren. Issue 6 (26th January 2016) - Grimes, Carley A.; Riddell, Lynn J.; Campbell, Karen J.; He, Feng J.; Nowson, Caryl A.
Abstract: Emerging evidence indicates that dietary Na may be linked to obesity; however it is unclear whether this relationship is independent of energy intake (EI). The aim of this study was to assess the association between Na intake and measures of adiposity, including BMI z score, weight category and waist:height ratio (WHtR), in a sample of Australian schoolchildren. This was a cross-sectional study of schoolchildren aged 4–12 years. Na intake was assessed via one 24-h urine collection. BMI was converted to age- and sex-specific z scores, and WHtR was used to define abdominal obesity. In children aged ≥8 years, EI was determined via one 24-h dietary recall. Of the 666 children with valid urine samples 55 % were male (average age 9·3 (sd 1·8) years). In adjusted models an additional 17 mmol/d of Na was associated with a 0·10 higher BMI z score (95 % CI 0·07, 0·13), a 23 % (OR 1·23; 95 % CI 1·16, 1·31) greater risk of being overweight/obese and a 15 % (OR 1·15; 95 % CI 1·09, 1·23) greater risk of being centrally obese. In the subsample of 8–12-year-old children ( n 458), adjustment for EI did not markedly alter the associations between Na and adiposity outcomes. Using a robust measure of daily Na intake we found a positive association between Na intake and obesity risk in Australian schoolchildren, which could not be explained by total energy consumption. To determine whether this is a causal relationship, longitudinal studies, with high-quality measures of Na and EI, are required.